ANALISIS PENERAPAN BASIS KAS MENUJU AKRUAL PADA LAPORAN KEUANGAN ENTITAS NIRLABA (STUDI KASUS: SEKOLAH SKN) - Khairuddin Pohan; Titi Suhartati; Elisabeth Yansye Metekohy (Politeknik Negeri Jakarta, 2019)
ANALISIS PENERAPAN BASIS KAS MENUJU AKRUAL PADA LAPORAN KEUANGANENTITAS NIRLABA (STUDI KASUS: SEKOLAH SKN) Khairuddin Pohan khairuddinpohan@gmail.comTiti Suhartati b_titis@yahoo.comElisabeth Yansye Metekohy lisayansye@yahoo.co.id Program Studi Akuntansi Keuangan Terapan Politeknik Negeri Jakarta ABSTRACT School are non-profit entities according to UU No.20 of 2003. The school also managed fundsindependently and performed accounting records that produce financial reports. The purpose of thisstudy was to determine the application of cash-based accounting recording methods in a non-profitentity namely the SKN school and used the method to be accrual-based according to PSAK No. 45.This research used qualitative with a case study approach at SKN school. The conclusion of this studyis there are still barriers about the preparation of financial statements on a cash-based accounting atthe